UTILIZATION OF GRAM-CHARLIER EXPANSIONS ON OPTION PRICING - (NIM : 20110020), MAULIDDIN
On this thesis, the option is calculated by using the Gram-Charlier expansion, which the Gram-Charlier expansion to approximate the density function of stock price returns. The results of this approximation is used to calculate the implied volatility by strike price and maturity time. In addition, the skewness and kurtosis as an element in the Gram-Charlier expansion is also calculated to find out how big the impact on option pricing. Evidence suggests that option pricing using Gram-Charlier expansion different from the Black-Scholes formula.